Development of Health Saving Competence for University Students - Valery Panachev (Journal of Global Pharma Technology, 2018)
The article reveals the author's approach to forming health-saving competence while studying at a university. The functions and principles of this competence formation are distinguished in the process of physical education, which will allow organizing the process of physical education at a higher level. Purpose of the study is to reveal features of forming health-saving competence of students in the process of physical education. The attainment of this goal is achieved with different theoretical and empirical method. Expanding functional connections and relations in educational work, we allocated functions of forming HSC for university students in the course of physical education. We have identified different principles and their use has allowed us to organize forming HSC on a higher level.Keywords: Functions, Principles, Components, and Psychological and Pedagogical Characteristics of Students' Health-Saving Competence Formation.